The Comparison of Pullout Strengths of Various Producing Methods for Internal Screw Threads of Additive Manufactured Metal Parts - Yarar, Eser; Ertürk, Alpay Tamer; Özer, Gökhan; Bulduk, Mustafa Enes (Springer, 2023)
Thread fastening is the primary method of joining components to construct a final product. Since thread coupling exists in many different industrial applications, this study aims to identify the proper manufacturing steps for achieving the highest mechanical fastening strength. This study reports the axial tensile force for removing screw threads from AM parts produced by following different threading routes. This study compares and evaluates the mechanical strength of diverse threaded specimens produced by additively produced and conventionally threaded AlSi10Mg parts. This study evaluates cube-shaped pieces produced by laser powder bed fusion. The main objective is to discover which type of production route ensures maximum thread stripping forces. The various process methods of internal screw threads were performed in 3 different printing inclinations.
Keywords: Laser powder bed fusion; AlSi10Mg; Drilling; Pullout strength